Liberal thought of Jose Faustino Sanchez Carrion - Vásquez Monge, Eduardo (2010)
José Faustino Sanchez Carrion integrates the Peruvian liberals first generation, which also belonged Hipólito Unanue, Mariano José de Arce, Jose Toribio Rodriguez de Mendoza and Francisco Javier Mariategui, and is recognized as the tribune of the Republic of Peru, which is the name given by Raul Porras Barrenechea, for his advocacy of the republican system against the proposed constitutional monarchy of general Jose de San Martin and his minister Monteagudo through the letters he signed with the pseudonym Sayan Solitaire. In his letters openly defends the republican system of government because this system was based on equality and freedom, which were the key components of a society of citizens, while the monarchy, however, is based on inequality and despotism and corresponded to a society of vassals. The war against the royalist forces and the difficult economic crisis of the old viceroyalty, conspired against the ideals of this first generation of Republicans who did not have the strength to establish a solid and efficient democratic system and facing the imminent danger to the Republic invited the Simon Bolivar to Peru to fight the royalists.